Effect of culture density in the growth and survival of fingerlings of black barrel Myloplus aylan (Pereira, Ota, Machado, Collins, Ândrade, Garcia-Ayala, Jégu, Farias & Hrbek, 2024) (Characiformes: Serrasalmidae) raised in aquariums - Guerra-Grandez, Franco Antonio (2025)
This study was conducted at the collection center of the "Los Leporinos" Association of Artisanal Fishermen of Ornamental Hydrobiological Resources in the town of Nina Rumi, Iquitos, Loreto Region, Peru. The objective was to evaluate the potential effects of stocking density on the growth and survival of fingerlings of black barrel Myloplus aylan (Pereira, Ota, Machado, Collins, Ândrade, Garcia-Ayala, Jégu, Farias & Hrbek, 2024). Nine glass aquariums were used, with a total of 180 fry weighing 1.47 g and measuring 4.09 cm in length. Feeding was 4 times per day (8, 11, 14, and 17 h), at a 6% feed rate, using a balanced pelleted diet with 50% protein. The zootechnical indices evaluated were: average daily gain (ADG), apparent feed conversion ratio (AFR), relative growth rate (RGR), specific growth rate (SGR), condition factor (K), coefficient of variation of weight (CVP), and survival (S). The experimental design was a completely randomized design to avoid edge effects. Three stocking densities were evaluated (T1 = 1 fish/20 L; T2 = 2 fish/20 L; and T3 = 3 fish/20 L). At the end of the study, growth indices such as ADG, SGR, and RGR were statistically influenced by the treatments, while no significant difference was found for AFR, with T1 apparently showing the best performance. The condition factor was also statistically influenced by the treatments, and survival was 100% in all treatments. In conclusion, T1 (1 fish/20 L) was the treatment that showed the best performance in terms of weight gain during 75 days of culture.